Richness and diversity of amphibians and reptiles in an altitudinal gradient at Sierra de Juarez, Chihuahua, Mexico. - Fernández López, Antonio; Lavín Murcio, Pablo Antonio (Instituto de Ecología, A.C., 2016)
This study was conducted from July 2004 to July 2005 in the Sierra de Juarez, in northern Chihuahua. This mountainous area is located west of Ciudad Juarez, is geographically isolated, by both natural features and anthropogenic influence. The objectives were todetermine the richness and diversity of amphibians and reptiles along an altitudinal gradient and thus contribute to a better understanding of their spatial distribution and abundance. Five hundred and eleven individuals of 16 species were recorded in 52 samplings. Ecological and environmental conditions that reveal the current status of this fauna and their potential use as indicators of disturbance are described.Knowledge of our study community is urgent, given the dynamic thatis beginning to show by invasions and changes being made in theSierra.